2022
DOI: 10.3389/fcvm.2022.846803
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Antithrombotic Treatment Patterns for Patients With Nonvalvular Atrial Fibrillation and Acute Coronary Syndrome or Underwent Percutaneous Coronary Intervention in China: A Cross-Sectional Study

Abstract: ObjectiveAntithrombotic therapy in patients with nonvalvular atrial fibrillation (NVAF) concomitant with the acute coronary syndrome (ACS) or underwent percutaneous coronary intervention (PCI) is challenging and has evolved in recent years. However, real-world data on this issue about antithrombotic regimens at discharge and its evolving trend were relatively scarce, especially in China.MethodsA total of 2,182 patients with NVAF and ACS/PCI were enrolled from 2017 to 2019. A total of 1,979 patients were finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
5
2
Order By: Relevance
“…However, those data are mostly based on Western populations, and Chinese studies have also shown that patients with high CHA 2 DS 2 -VASc scores have a high stroke risk. 31,49 There was a significant difference between the CHA 2 DS 2 -VASc score in our study and that reported in other studies, 12 with an average score of 4.6 points, most likely reflecting the age of patients who were older than 65 years and exhibited more comorbid conditions, including hypertension, diabetes and prior strokes/TIAs. In this study, we found that the CHA 2 DS 2 -VASc score was significantly related to the occurrence of MACCEs in elderly patients, and those patients who received ATT were less prone to MACCEs.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…However, those data are mostly based on Western populations, and Chinese studies have also shown that patients with high CHA 2 DS 2 -VASc scores have a high stroke risk. 31,49 There was a significant difference between the CHA 2 DS 2 -VASc score in our study and that reported in other studies, 12 with an average score of 4.6 points, most likely reflecting the age of patients who were older than 65 years and exhibited more comorbid conditions, including hypertension, diabetes and prior strokes/TIAs. In this study, we found that the CHA 2 DS 2 -VASc score was significantly related to the occurrence of MACCEs in elderly patients, and those patients who received ATT were less prone to MACCEs.…”
Section: Discussioncontrasting
confidence: 48%
“…Ischemic strokes among AF patients without anticoagulation, measured by the CHA 2 DS 2 ‐VASc score, were reported at 0.44% to 4.0% over all, 39,40 patients at low risks 37,38,41,42 were treated with 0% to 0.95%, those with intermediate risks 43–45 were treated with 0.10% to 6.6%, and those at high‐risk 46–48 were treated with 2.4% to 6.2% from prior studies. However, those data are mostly based on Western populations, and Chinese studies have also shown that patients with high CHA 2 DS 2 ‐VASc scores have a high stroke risk 31,49 . There was a significant difference between the CHA 2 DS 2 ‐VASc score in our study and that reported in other studies, 12 with an average score of 4.6 points, most likely reflecting the age of patients who were older than 65 years and exhibited more comorbid conditions, including hypertension, diabetes and prior strokes/TIAs.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…However, in patients with AF undergoing lower-extremity revascularisation, antithrombotic strategies remain a challenge in clinical practice. The risk of ischaemic and haemorrhagic events must be carefully balanced ( 15 ). In patients with AF and PAD, there is a significant 56% reduction in the incidence of acute limb events when receiving rivaroxaban compared with that when receiving warfarin ( 1 ), and current clinical practice is more inclined to the use of NOACs, such as rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have focused on the issue of reduced rivaroxaban doses in Asian populations. Asians are more prone to anticoagulant-related and intracranial bleeding than Caucasians owing to differences in race and lifestyle ( 15 ). Another study showed that in healthy Chinese individuals, 10 mg rivaroxaban may be sufficient to reach 83% of inhibition of factor Xa activity caused by a 20-mg dose ( 17 ).…”
Section: Discussionmentioning
confidence: 99%